The Analysis of Corporate Bond Valuation under an Infinite Dimensional Compound Poisson Framework - Sheng Fan (Abstract and Applied Analysis)
This paper analyzes the firm bond valuation and credit spread with an endogenous model for the pure default and callable default corporate bond. Regarding the stochastic instantaneous forward rates and the firm value as an infinite dimensional Poisson process, we provide some analytical results for the embedded American options and firm bond valuations.